2014
DOI: 10.2459/jcm.0b013e32836411d6
|View full text |Cite
|
Sign up to set email alerts
|

C-reactive protein and subclinical cardiovascular disease among African−Americans

Abstract: Objective Systemic inflammation has been implicated as an early marker for subclinical cardiovascular disease; however, findings have been inconsistent in the African American population. Methods We examined the relation of C-reactive protein to subclinical disease in African American participants of the Jackson Heart Study first examination. Subclinical disease evaluated included aortic valve calcification (AVC), carotid intima-medial thickness (IMT) and peripheral arterial disease (PAD). We assessed the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…High CRP levels are reported a potential indicator of subclinical atherosclerosis . Hashimoto et al performed carotid artery ultrasonography and measured Hs‐CRP levels in patients aged 40‐79 years with cardiovascular risk factors and found that Hs‐CRP is a marker of atherosclerotic activity in the early stages of the disease .…”
Section: Discussionmentioning
confidence: 99%
“…High CRP levels are reported a potential indicator of subclinical atherosclerosis . Hashimoto et al performed carotid artery ultrasonography and measured Hs‐CRP levels in patients aged 40‐79 years with cardiovascular risk factors and found that Hs‐CRP is a marker of atherosclerotic activity in the early stages of the disease .…”
Section: Discussionmentioning
confidence: 99%
“…Smoking triggers chronic immunologic responses that upregulate biomarkers associated with inflammation and multi-organ disease, including plasma C-reactive protein (CRP) [ 1 3 ]. This, coupled with the relatively low smoking cessation rate (~3 %) among U.S. adults underscores the importance of daily smokers engaging in health-enhancing behaviors such as physical activity and healthy eating [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…The DCC provided three online and five onsite workshops, developed/distributed more than 250 copies of the booklet and posted instructions on the RTRN website to facilitate the data utility. Five related manuscript proposals, eleven presentations, seven published papers [ 46 , 47 , 48 , 49 , 50 , 51 , 52 ] and two R01 and two small (R03 and R21) grant proposals were supported.…”
Section: Discussionmentioning
confidence: 99%